Di Balik Layar: Interpretasi Artistik Pengendalian Diri Penderita Smiling Depression - Safitri, Mesy Nadia; Loravianti, Susasrita; Ilham, Kurniadi; Emri, Emri (Institut Seni Indonesia Padangpanjang, 2025)
The dance work Behind the Screen is inspired by a social phenomenon, namely Smiling Depression, a term that refers to a person with depression who looks smiling when experiencing problems, this is often found in social life, they will look normal and happy in living their lives, and will even convince others that they are fine. The creator describes this idea in group choreography using seven female dancers as an interpretation of the different forms of self-control of people with Smiling Depression. The creation of the dance work Behind the Screen provides awareness for someone suffering from Smiling Depression who can control themselves so that it does not have a negative impact on life. This work uses the Alma M. Hawkins dance creation approach in the book